Meta-analysis of the acute effects of anodal transcranial direct current stimulation on athletic performance - Jiang, Mi; Liu, Yang; Gao, Xu (Frontiers in Physiology, 2025)
ObjectiveSystematically evaluate the acute effects of anodal transcranial direct current stimulation (a-tDCS) on athletes’ sport-specific performance and identify the optimal stimulation parameters and target brain regions for enhancing sport-specific performance.MethodsSearch PubMed, Web of Science, CNKI, Wanfang, and other databases to include randomized controlled trials studying the effects of anodal tDCS on sports performance in healthy athletes. Use a random-effects model to calculate the standardized mean difference (SMD), assess heterogeneity, and evaluate influencing factors. Additionally, conduct three subgroup analyses: (1) based on stimulated brain areas (M1, PFC, TC, CB); (2) based on different sports performance domains (endurance, strength, precision skill tasks, competitive-collaborative skills) for cluster analysis; (3) tDCS protocol parameters (current intensity and stimulation duration).ResultsThis study included 31 articles, covering 473 athletes. The meta-analysis results showed that the acute effect of a-tDCS significantly improved athletes’ specific sports performance, with a moderate effect size (SMD = 0.39, 95% CI = 0.23–0.54, p < 0.001). Subgroup analysis revealed that M1 stimulation had the most consistent effect (SMD = 0.32, 95% CI = 0.15–0.48, p < 0.001), followed by PFC stimulation (SMD = 0.39, 95% CI = 0.03–0.76, p = 0.03). a-tDCS significantly enhanced athletes’ endurance performance (SMD = 0.46, 95% CI = 0.20–0.72, p < 0.001) and competitive-collaborative skill tasks (SMD = 0.45, 95% CI = 0.10–0.80, p = 0.01). Analysis of stimulation parameters indicated that a moderate current intensity of 1.6–2.0 mA (SMD = 0.38, p < 0.001) and a stimulation duration of 16–20 min (SMD = 0.45, p < 0.001) were the optimal protocols for enhancing sports performance.ConclusionThe acute effects of a-tDCS significantly enhance athletes’ endurance and competitive-collaborative skill performance, particularly when targeting the M1 and PFC regions. The optimal stimulation protocol involves a moderate current intensity (1.6–2.0 mA) and duration (16–20 min). Future research should further optimize stimulation parameters and explore long-term effects to enhance the application of a-tDCS in sports training.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=103158, identifier CRD42025103158.